Right-Sided Infective Endocarditis and Pulmonary Infiltrates: An Update. Issue 5 (September 2016) - Chahoud, Jad; Sharif Yakan, Ahmad; Saad, Hala; Kanj, Souha S.
Abstract : Sixty years after its initial description, right-sided infective endocarditis (RSIE) still poses a challenge to all medical practitioners. Epidemiological data reveal a rising incidence attributable to the global surge in the number of intravenous drug users and the increased use of central vascular catheters and implantable cardiac devices. RSIE differs from left-sided infective endocarditis in more than just the location of the involved cardiac valve. They have different clinical presentations, diagnostic findings, and prognoses; hence, they require different management strategies. Cardiac murmurs and systemic emboli are usually absent in RSIE, whereas pulmonary embolism and its related complications dominate the clinical picture. Diagnostic delay of RSIE is secondary to the similarity in its initial presentation to other entities. Complications may ensue as a result of this delay. Diagnosis can be initially confirmed by using transthoracic echocardiography, except in patients with implanted cardioverter defibrillator, where a transesophageal echocardiogram is necessary. Various factors may increase mortality and morbidity in RSIE such as tricuspid valve vegetation size, fungal etiology, and low CD4 cell count in HIV patients. Oxacillin and vancomycin had been the traditionally used agents for the treatment of methicillin-susceptible and methicillin-resistant Staphylococcus aureus, respectively. More recently, daptomycin has shown promising results, which has led to its Food and Drug Administration (FDA) approval for the treatment of S. aureus bacteremia and associated RSIE. The aim of this article is to provide a comprehensive update on RSIE including epidemiology, pathogenesis, microbiology, diagnosis, management, and prognosis.